Hubungan Industrial dalam Perspektif Pancasila - Siswanto, Dwi (Jurnal Filsafat "WISDOM", 1999)
This research aims to describe and provide any more comprehensive understanding of the Industrial Relationship in Pancasila Perspective. This is important since it has a strategical dimension in the life of nation and it will supply some contributions of judgement for the attempt of labor condition, improvement in Indonesia as a whole.This a library research and it completes the inquiries that have been done. The method adopted in analyzing the result of this study is hermeneutics with the following features: description, interpretation, holistic, heuristic, and reflection.The results of this research are shown as follows:1. The industrial relationship in the Pancasila Perspective is an antropocentric type, that is, man are placed in the center as subject and object.2. The industrial relationship in the Pancasila Perspective places "man as such" as a goal that ought to reach.3. "Man as such" in the Pancasila Perspective is: (a) an ideal type of man, the ideal human being is the subject as carrier and actor Pancasila, he will be able to self rehance and work at every condition to devolp his society, suks to a material and spiritual will being society; (b) The concrete man, that being and exist in everyday life, he bring many dimension: personal, relational, and structural; (c) The prosperous man in his life, in some aspect: religuously, cultural, and social.